Mapping Research on Language, Media, and Violence in Indonesia: A Bibliometric and Systematic Literature Review - Yusri Yusri; Jose Cristina Parina (Universitas Negeri Makassar, 2026)
Abstract. This study seeks to investigate the evolution of language, media, and violence studies in Indonesia through a bibliographic analysis and a Systematic Literature Review (SLR) of national journal articles indexed by Garuda. Employing the SLR approach, the research adheres to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) framework. Data were gathered from national journal articles addressing the intersections of language, media, and violence, and were analyzed using bibliographic and thematic methods. The findings indicate a significant increase in research regarding language, media, and violence in recent years, particularly with the rise of digital and social media. The predominant research themes identified include cyberbullying, hate speech, verbal violence, and victim blaming. Social media emerges as the primary focus of study, while the qualitative approach, particularly critical discourse analysis and pragmatics, is the most commonly utilized methodological framework. Furthermore, the research reveals that the exploration of language, media, and violence in Indonesia is progressing in a multidisciplinary manner, incorporating insights from linguistics, communication, education, and media studies. Nevertheless, there remains a relative scarcity of research on the long-term impacts of linguistic violence, the role of Artificial Intelligence (AI), and comprehensive, multidisciplinary approaches. This study provides a comprehensive overview of trends and future directions in the field of language, media, and violence studies in Indonesia, serving as a valuable reference for further exploration in the context of the digital society Keywords: Language, Media, Violence, Systematic Literature Review, Bibliographic Analysis, Garuda